Effects Of Coupling Agents On The Properties Of Poly(Methyl Methacrylate)/Hydroxyapatite Composites For Denture Base Application - Tham, Wei Ling (2011)

(untitled)
Poly(methyl methcrylate) (PMMA) composites containing 5 wt% hydroxyapatite (HA) was prepared by using heat-processing polymers powder and liquid method. In phase 1, both PMMA and HA powder were grounded using planetary ball milling. The effects of the grinding time and particle size of the PMMA/HA powder on the flexural properties and morphology of the composites was investigated. The suitable grinding time is 90 min. For the planetary ball mill-ground PMMA/HA powder, the flexural modulus of the respective PMMA composites was slightly increased. Planetary milling is capable of increasing the surface area of fine particles in the composites specimens, which resulted in a more homogeneous distribution of HA and a reduction of void contents in PMMA matrix.